The Effects of Silica/Carbon Black Ratio on the Dynamic Properties of the Tread compounds in Truck Tires - Ramin Zafarmehrabian; Saeed Taghvaei Gangali; Mir Hamid Reza Ghoreishy; Mehran Davallu (E-Journal of Chemistry)
NR is the major constituent in the rubber compound used for the tread on the truck tires. A general compound formulation of the tire tread includes NR and BR as polymer base and carbon black as the reinforcing filler, and curative components. In this paper the effects of dual filler system (carbon black and precipitated silica) on the dynamic properties of tire treat has been studied. The results show by increasing of precipitated silica, significant improvement was observed in fatigue resistance, rolling resistance and heat buildup of the tire. Tensile strength and modulus and wet grip of tire tread decrease with increasing of silica in rubber compound formulation.